Short Term Effects of Muscle Energy Technique vs. Active Release Technique in Improving Hamstring Flexibility and Pain in Patients with Acute Anterior Cruciate Ligament (ACL) Tear - A Randomized Control Trial - Gaur, Vibhuti Vinodsingh; Kapoor, Angela Arun; Phansopkar, Pratik Arun (Journal of evolution of medical and dental sciences, 2021)
BACKGROUND Hamstring tightness is a very commonly occurring condition. Poor hamstring flexibility is usually associated with injuries to the lower back and lower extremities. Active release technique and muscle energy technique both help in improving hamstring flexibility and pain in patients with acute anterior cruciate ligament (ACL) tear. While muscle energy technique (MET) is usually used by practitioners and manual therapists, there are only few studies supporting and accepting its use, as well as very few evidences to validate the theories used to elaborate the potency of muscle energy techniques. This has encouraged many researchers to find the benefits of other types of stretching on sport performance. The objective of this study is to compare the benefit of active release technique (ART) and MET in improving flexibility of hamstrings. METHODS 60 subjects were divided into three groups. The muscle energy technique group included 5-minute warm-up followed by MET routine for 6 minutes and ART group included 5-minute warm up followed by an ART routine for 6 minutes. The subjects performed all the routines on three separate days. RESULTS Data analysis showed no significant difference (p < 0.569) in hamstring muscle flexibility following muscle energy techniques and active release technique types of stretching. CONCLUSIONS Both the techniques muscle energy technique and active release technique are equally effective. KEY WORDS Hamstring, Flexibility, Stretching, MET, ART, Muscle Force, Pain